Impact of different selection policies on subcutaneous ICD implants and therapies. Issue 6 (23rd May 2020) - Harding, Idris; Kaura, Amit; Yue, Arthur; Roberts, Paul; Murgatroyd, Francis; Scott, Paul A
Abstract: Background: Patients with existing or anticipated indications for cardiac resynchronisation therapy (CRT), bradycardia, or anti‐tachycardia pacing should not be offered subcutaneous defibrillators (SQIDs) but it remains unclear how clinicians should predict future need for these therapies. Methods: We applied three SQID selection policies to data collected retrospectively from transvenous implantable cardioverter defibrillator (TV‐ICD) implants: (a) approach A, SQID used in inherited channelopathies and idiopathic ventricular fibrillation only; (b) approach B, as above, plus all hypertrophic cardiomyopathy and grown‐up congenital heart disease patients; (c) approach C, as above, plus primary and secondary prevention (for ventricular fibrillation only) of SCD in patients with QRS <150 ms. Approach C reflects current ESC and AHA/ACC/HRS guidelines. Results: 338 of 951 patients with TV‐ICD were considered for SQID after excluding 613 patients with contraindications. Approaches A, B, and C yielded 45 (4.7%), 89 (9.4%), and 338 (35.5%) patients suitable for SQID, respectively. Use of SQID resulted in more frequent ICD shocks compared to TV‐ICD with approach C only (0.43 vs 0.23 per 1000 patient‐days; P = .03). Rates of CRT upgrade were comparable across selection criteria (0, 0.03, and 0.07 per 1000 patient‐days for approaches A, B, and C, respectively; P = NS). Risk of early mortality was higher when more liberal inclusion criteria were used ( P = .003). Conclusions: One in three patients receiving ICDs may be suitable for SQID under current ESC and AHA/ACC/HRS guidelines. This proportion is influenced significantly by the selection criteria used, and the criteria used by a physician should be informed by the estimated survival of the patient, risk of shocks for MVT, future pacing, and CRT requirements.